Socio-Economic Studies in Beef Cattle and Corn Crop Business - Supardi Rusdiana; Angga Ardhati Rani Hapsari (SOCA: Jurnal Sosial Ekonomi Pertanian, 2020)
The purpose of this research was to analyze the economic value of farmers in beef cattle business and corn crop business. The research was conducted in Pallangga Village, Pallangga Sub-District, Gowa Regency, South Sulawesi in 2018. The research used a survey method and interviews with 26 farmers. The research method used a statistical analysis of t-test and economic value of R/C. Primary and secondary data were analyzed descriptively, quantitatively and economic analysis. The results showed that the results of the t-test analysis of the average similarity at 99% confidence level, there was a significant difference between the number of beef cattle and land area, a significance of 0,000 smaller (P <0.05). Farmer education had no significant effect on the 95% confidence level, because it was supported by the experience of farmers which was quite high (P>0.05). Farmer labor had a significant effect on the level by 99% and had a positive effect on beef cattle and corn plant. It was supported by the age of farmers who were still productive, so farmers were able to increase working time. Net profit from beef cattle business was Rp.4.85 million/year, equivalent to Rp.404,166/month with R/C of 1.92. The net profit from corn crop business was Rp.5.88 million/year, equivalent to Rp.404,166/month with R/C of 1.97. These results indicated the t-test value as a variable that significantly affected (P> 0.05). In terms of economic value, beef cattle and corn crop business in farmers with an R/C value > 1, it can be said that the business was feasible to be maintained.